PENGARUH KELEKATAN GURU DAN PESERTA DIDIK TERHADAP MOTIVASI MENGHAFAL AL-QUR’AN PESERTA DIDIK KELAS VIII PADA MATA PELAJARAN BTQ DI MTS MADANI ALAUDDIN PAOPAO - Murti, Maulidia; La Ode Ismail Ahmad; Syamsuri; Muhammad Rusmin B; Mappasiara (Jurnal Diskursus Islam, 2024)
This thesis aims to: 1) Describe the influence of teacher and student attachment on the motivation to memorize the Qur’an of students in the BTQ subject at MTs Madani Alauddin Paopao; 2) Describe the motivation to memorize the Qur’an of students at MTs Madani Alauddin Paopao; 3) Analyze the influence of teacher and student attachment on the motivation to memorize the Qur’an of students in the BTQ subject at MTs Madani Alauddin Paopao. This type of research is quantitative research using the ex post facto method with a simple paradigm research design. The respondents in this study numbered 150 people with a sampling technique of simple random sampling of 30 students. Based on the results of descriptive statistical analysis, it can be concluded that: teacher and student attachment is in the moderate category with a percentage of 70% while the motivation to memorize the Qur’an of students at MTs Madani Alauddin Paopao is also in the moderate category with a percentage of 73%. From the results of the analysis, the real level (α) and table value were obtained at 5% or 0.05. Where the results of the analysis were obtained tcount = 2.930 while the ttable value = 1.701 for 30 samples which can be interpreted that tcount> ttable, namely 2.930> 1.701. Thus, the attachment of teachers and students influences the motivation to memorize the Qur’an of students at MTs Madani Alauddin Paopao, namely 16.8% while the remaining 83.2% is influenced by other variables. The implications of this study are for students to focus more on the relationship between teacher and student attachment. For teachers, to be able to find things that make students not bored during the learning process in memorizing the Qur’an. For schools, to be able to be used as evaluation material for the attachment of teachers and students to increase the motivation to memorize the Qur’an of students.